(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the positive and negative consequences of using artificial intelligence in education, discusses the emergence, development, and potential of artificial intelligence systems in the field of education, and discusses ways to improve the quality of education through their application in the educational process.